Year Abroad (A Dialogue) - James Illingworth; Akiko Furukawa; Mark Gant; Guy Puzey (Modern Languages Open, 2023)
This article is the product of an exchange that took place over the course of two months between March and May 2023 and offers reflections on how the year abroad in Modern Languages has changed as a result of the COVID-19 pandemic. The four contributors each bring a distinct expertise in year abroad provision and represent different language areas and geographical regions of the United Kingdom. The core themes explored in the discussion are the need for flexibility and resilience in degree programmes, the importance of accessibility and inclusion, and the challenges and opportunities of digital developments in a mobilities context. As well as reflecting on the impact of the pandemic on year abroad provision, the contributors also dwell on how the UK’s withdrawal from the European Union has altered the year abroad landscape.